2007
DOI: 10.1080/13574800701306179
|View full text |Cite
|
Sign up to set email alerts
|

A New Urban Planning Approach for the Regeneration of an Historical Area within Istanbul's Central Business District

Abstract: This study is based on a research project for the urban regeneration of an old historical region in the central business district. This district, where the Golden Horn meets the Bosphorus, is known as Galata and is accepted as part of the world's cultural heritage. Although historically Galata has played a significant role in Istanbul due to its location, recently it has been deteriorating rapidly because of vandalism and lack of care. Through an objective assessment of the problems and constraints of this his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…This is also a valuable suggestion, since SDG 16 aims to promote accountable and inclusive institutions as well as peaceful societies. Monitoring such vandal acts that might be in various forms, including graffiti or looting (Vella et al, 2015), will inform policy makers to develop effective urban regeneration projects (Eyüboğlu et al, 2007).…”
Section: Id Questionmentioning
confidence: 99%
“…This is also a valuable suggestion, since SDG 16 aims to promote accountable and inclusive institutions as well as peaceful societies. Monitoring such vandal acts that might be in various forms, including graffiti or looting (Vella et al, 2015), will inform policy makers to develop effective urban regeneration projects (Eyüboğlu et al, 2007).…”
Section: Id Questionmentioning
confidence: 99%
“…Hillier and Lida [27] examined the correlation used in graphical measurements of the street network in space syntax studies, the representation of axes and the observation of movement patterns, answering how people find their way in a complex urban structure and how they benefit from space. Using the space syntax method, Eyüpo glu et al [28] identified strategic axes for development and change in the historical center of Istanbul Galata and key areas for renewal, and proposed special design solutions to revitalize this area. Hillier [29] states that in the productive phase of design, what is needed to maximize architectural creativity is ideas about formal and spatial configuration that are as comprehensive as possible about specific formulas in order to leave the solution space as open as possible to creative invention.…”
Section: Introductionmentioning
confidence: 99%
“…Ο εξευγενισμός μιας περιοχής πρέπει πάντα να λαμβάνει υπόψη και τις ευρύτερες αλλαγές που θα φέρει στον αστικό χώρο της πόλης (Smith 1986). Όπως για παράδειγμα ο εξευγενισμός του Γαλατά στην Κωνσταντινούπολη, δεν είχε συνέπειες μόνο τοπικά αλλά και ευρύτερα επίδρασε στο οικονομικό κοινωνικό status της πόλης (Eyubolu E. et al 2007). Επίσης, επηρεάζει τόσο τους γηγενείς κατοίκους όσο και τους νεοεισερχόμενους τόσο θετικά όσο και αρνητικά (Huynh and Maroko 2013).…”
Section: επιστημολογία του εξευγενισμούunclassified